A retrospective analysis of the long-term test–retest stability of pain descriptors of the painDETECT questionnaire. (1st February 2016) - Keller, T.; Freynhagen, R.; Tölle, T.R.; Liwowsky, I.; Möller, P.; Hüllemann, P.; Gockel, U.; Stemmler, E.; Baron, R.
Abstract: Objective: PainDETECT (PD-Q) is a patient reported screening questionnaire to identify patients with neuropathic pain based on questions regarding typically sensory symptoms of neuropathic pain. The aim of the present investigation was to assess the test–retest stability of pain descriptors of the PD-Q within a time window of 1–3 weeks. Methods: Data sets of 74 chronic pain patients sampled in an open pain register at two visits were analyzed and compared. Patients with change of pain localization between visits were excluded from analysis. Beside conventional measures (Pearson correlation coefficient r, intraclass correlation coefficient ICC, kappa), also calculated measures known from method comparison were used. Results: The mean duration between visits was 15 days. The measures were in the range of r  = 0.72–0.86, ICC = 0.71–0.86, and kappa = 0.62–0.72 for PD-Q pain descriptors (burning, prickling, mechanical allodynia, pain attacks, thermal hyperalgesia, numbness, pressure induced pain). Conclusion: The individual PD-Q pain descriptors showed accurate test–retest stability as a prerequisite for use in repeated measurements (e. g. post baseline or follow up data) in clinical trials.